Relationship Between Maternal Age, Education, and Parity in The Incidence of Spontaneous Abortion in Bali - I Made Wira Supanji; Anak Agung Raka Budayasa; Pande Ayu Naya Kasih Permatananda; Putu Nita Cahyawati; Anak Agung Sri Agung Aryastut (Science Midwifery, 2022)
Abortion is one of the problems in the world that affects the health, morbidity, and mortality of pregnant women. The purpose of this study was to examine the relationship between maternal age during pregnancy, education, and maternal parity in the incidence of spontaneous abortion at the Sanjiwani Hospital, Gianyar. This research was a retrospective and cross-sectional analytic study. The inclusion criteria were pregnant women who performed prenatal care at the Obstetrics Gynecology section of the Sanjiwani Hospital Gianyar, were clearly diagnosed with abortion (incomplete, complete, insipient) and/or non-abortion, and had complete pregnancy data. This study succeeded in collecting 79 data on pregnant women who met the inclusion and exclusion criteria. From the 79 data, 39 pregnant women experienced spontaneous abortion, and 40 pregnant women did not experience abortion. The results of bivariate analysis using chi-square showed a significant relationship between the age of pregnant women, education, and parity in the incidence of spontaneous abortion with a P value <0.05. This research is expected to be the basis of health promotion for pregnant women in order to increase the understanding of risk factors of spontaneous abortion and be able to take appropriate prevention.